War Termination as a Civil-Military Bargain - Cochran, Shawn T. author. aut Link
XI, 220 p.
Keywords: War termination reflects a civil-military bargain and affects relevant decisions made by political leaders. For the leader embroiled in protracted war, this risk dictates whether he or she will commit more resources to the fight or else cut the state's losses and get out.